Penerapan Inverse Manufacturing dalam Penanganan Produk Lampu Hemat Energi - Loice, Romy; Arthaya, Bagus Made; Prasetyo, Harry (Universitas Katolik Parahyangan, 2016)
Lighting is one of the human basic needs that must be fullfiled. Compact fluorescent lamps is the most used lamp as source of lighting. However, they contain mercury, which is classified as heavy metals, that can potentially harm the environment. Even as mercury container, many people didnt know that. Many people dont know the method to handle the broken or used compact fluorescent lamp. They just dispose the broken compact fluorescent lamp to trash without considering the effect of mercury contained.Inverse Manufacturing concept is about designing product life cycle that aims to repair and reuse product components so that the negative impact can be reduced and minimized. In this research, the concept of Inverse Manufacturing is applied on handling the compact fluorescent lamp product in Bandung, West Java. The study is begun with designing the Inverse Manufacturing conceptâs model by adding the step of collecting back (two scenarios), sorting, repairing, remanufacturing, and recycling into the life cycle of compact fluorescent lamp. The results of recycling rates of 15 Watt compact fluorescent lampÂ (about 234 grams) starts from the lowest value,Â and the maximum value are 27,51 % (64,366 grams),Â and 27,61 % (64,609 grams). By applying this concept, the result are the reduction on the amount of compact fluorescent lamp waste dumped into the environment and the achievement ofÂ the conservation of natural resources through the reuse of used components.